1987
DOI: 10.1111/j.1439-037x.1987.tb00277.x
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Faba Bean (Vicia faba L.) Plants as Affected by Glyphosate

Abstract: Two field experiments were carried out during 1982/83 and 1983/84 seasons at Experimental Farm of National Research Centre at Shalakan, Kalubia Governorate, Egypt, to study the reversal effect of glyphosate induced phytotoxicity on growth and yield and its components of faba bean by the application of growth factors, i.e., growth regulators, amino acids and nutrient elements at different concentrations. A split plot design with four replications was used in both seasons. The obtained results indicated clearly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 4 publications
1
5
1
Order By: Relevance
“…This is also in line with the findings of Michel et al (2016) and Labri et al (2013) who also observed no significant difference in the number of leaves produced by plants at different concentrations of glyphosate when compared with control. It is at variance with the findings of Shaban et al (1987) who reported an increase in the number of branches and leaves per plant in faba beans at high doses of glyphosate.…”
Section: Effects Of Glyphosate and Bacterial Inoculants Oncontrasting
confidence: 50%
“…This is also in line with the findings of Michel et al (2016) and Labri et al (2013) who also observed no significant difference in the number of leaves produced by plants at different concentrations of glyphosate when compared with control. It is at variance with the findings of Shaban et al (1987) who reported an increase in the number of branches and leaves per plant in faba beans at high doses of glyphosate.…”
Section: Effects Of Glyphosate and Bacterial Inoculants Oncontrasting
confidence: 50%
“…This however, comes at an expense, where signs of phytotoxicity effects of the herbicide start showing on the faba bean plants, including leaf wrinkling and chlorosis . Fortunately, these effects could be reversed by improving the host's nutritional status after spraying (Shaban et al 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of Vicia faba with either gibberellic acid (GA3 at 50 ppm) alone or in mixture with cytokinin reversed the phytotoxic effect of glyphosate herbicide. (Shaban et al 1987). Foliar nutrient solutions containing N, P, K, Mn, Zn, B and Mo resulted in partial recovery of the negative herbicide effects on photosynthetic rate in Zea mays, Triticum aestivum and Glycine max under field condition (Haley 2017).…”
Section: Introductionmentioning
confidence: 99%